FAKTOR SOSIOLOGIS QAŪL QADĪM DAN QAŪL JADĪD (ANALISIS EKSPEDISI INTELEKTUAL IMAM SYAFI’I) - M. Chiar Hijaz; St. Risnawati Basri; Zainal Abidin (Universitas Islam Negeri Alauddin Makassar, 2023)
This research examines the social aspects of the dynamics of qaul qadim and qaul jadid of Imam Syafi'i. The main mission of this research is to get to know the figure of Imam Syafi'i, to see the dynamics of his thinking and the sociological factors behind the dynamics of his thinking. This type of research is descriptive qualitative research, because it accommodates concepts and ideas in information management. The information base studied came from a prominent scholar, namely Imam al-Shafi'i. The collected information is processed using a qualitative method, after which it is analyzed using critical analysis. The results of the research show that the figure of Imam Shafi'i was born in Gazza (a region near Palestine) in 150 H-204 H. In the phase of the journey of thought of Imam Shafi'i (Iraq and Egypt) gave birth to a concept of thought called qaul qadim and qaul Jadid. According to some opinions, the trigger for the dynamics of al-Shafi'i's view is due to: Differences in verses or hadith used as evidence; Viewpoints in mastering verses or hadiths that are not the same; Comparison of thoughts on the existence of ijma'; Comparison of asl (principal) and illah (reason) on the qiyas used and comparison of thoughts on the position of qaul shahabi. Apart from that, other aspects that sparked al-Syafi'i's view were Geographical Aspects, Cultural/ Customs Aspects and Scientific Aspects.